Adjustment problems faced by international students in South Africa - Mokgwasi, Kegomoditswe Morongwa (My University, 2017)
The aim of the study was to assess the challenges faced by international students in South Africa. The study was conducted at the University of the Witwatersrand in Johannesburg. There were 14 international students who participated in the study. Of these, 6 were male and 8 were female. The study was qualitative in nature. An interview schedule was used to interview participants. Thematic content analysis was used to analyse data. The results showed that international students in South Africa faced adjustment challenges relating to: reasons for choosing to study in South Africa, first settling in experiences, financial constraints, registration process, language problems, visa application and immigration laws, cultural differences, diversity, discrimination, academic challenge, homesickness, social support, institutional assistance and how they handled the challenges to cope with the prevailing situation in South Africa. Future studies should thus focus on finding effective ways to improve the adjustment process for international students in South Africa.
A research report submitted in partial fulfillment of the requirements for the degree of Masters in Psychology by Coursework and Research Report in the field of Organisational Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg March 2017
Keywords: International education--South Africa; Education, Higher--International cooperation; Education and globalization--South Africa; Universities and colleges--South Africa